The enrichment of maternal environment prevents pre-term birth in a mice model - Schander, Julieta Aylen (2020)
Maternal lifestyle affects both mother health and pregnancy outcome in humans. Several studies have demonstrated that interventions oriented toward reducing stress and anxiety have positive effects on pregnancy complications such as preeclampsia, excessive gestational weight, gestational diabetes and preterm birth. In this work, we showed that the environmental enrichment (EE), defined as a noninvasive and biologically significant stimulus of the sensory pathway combined with voluntary physical activity, prevented preterm birth (PTB) rate by 40% in an inflammatory mouse model induced by the systemic administration of bacterial lipopolysaccharide (LPS). Furthermore, we found that EE modulates maternal metabolism and produces an anti-inflammatory environment that contributes to pregnancy maintenance. In pregnant mice uterus, EE reduces the expression of TLR4 and CD14 (the LPS receptor and its coactivator protein), preventing the LPS-induced increase in PGE2 and PGF2α release and nitric oxide synthase (NOS) activity. In cervical tissue, EE inhibits cervical ripening events, such as PGE2 release, matrix metalloproteinase (MMP)-9 increased activity and neutrophil recruitment, therefore conserving cervical function. It seems that EE exposure could mimic the stress and anxiety-reducing techniques mentioned above, explaining, at least partially, the beneficial effects of having a healthy lifestyle before and during gestation. Furthermore, we propose that designing an EE protocol for humans could be a noninvasive and preventive therapy for pregnancy complications, averting pre-term birth occurrence and dreaded sequelae that are present in the offspring born too soon.